1990
DOI: 10.1002/jcp.1041420303
|View full text |Cite
|
Sign up to set email alerts
|

Adenine nucleotides modulate phosphatidylcholine metabolism in aortic endothelial cells

Abstract: ATP and ADP, in concentrations ranging from 1-100 microM, increased the release of [3H]choline and [3H]phosphorylcholine (P-choline) from bovine aortic endothelial cells (BAEC) prelabelled with [3H]choline. This action was detectable within 5 minutes and was maintained for at least 40 minutes. ATP and ADP were equiactive, and their action was mimicked by their phosphorothioate analogs (ATP gamma S and ADP beta S) and adenosine 5'-(beta, gamma imido) triphosphate (APPNP), but not by AMP, adenosine, and adenosin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1991
1991
2001
2001

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 55 publications
3
17
0
Order By: Relevance
“…Activation of phospholipase C has been clearly demonstrated for nucleotide receptors in BAME cells (this paper), PC12 cells (Murrin & Boarder, 1992), hepatocytes (Keppens et al, 1992), airway epithelial cells (Brown et al, 1991) and sheep anterior pituitary cells (Davidson et al, 1990). Phospholipase D activation has been reported by ourselves and others (Martin & Michaelis, 1988;Pirotton et al, 1990) to be a consequence of purinoceptor stimulation of large vessel endothelium. We have recently shown that these cells contain a mixture of both P2y and nucleotide receptors , and so the phospholipase D response may in part be a nucleotide receptor response.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Activation of phospholipase C has been clearly demonstrated for nucleotide receptors in BAME cells (this paper), PC12 cells (Murrin & Boarder, 1992), hepatocytes (Keppens et al, 1992), airway epithelial cells (Brown et al, 1991) and sheep anterior pituitary cells (Davidson et al, 1990). Phospholipase D activation has been reported by ourselves and others (Martin & Michaelis, 1988;Pirotton et al, 1990) to be a consequence of purinoceptor stimulation of large vessel endothelium. We have recently shown that these cells contain a mixture of both P2y and nucleotide receptors , and so the phospholipase D response may in part be a nucleotide receptor response.…”
Section: Discussionsupporting
confidence: 53%
“…Phospholipase D is also activated I Author for correspondence. in large vessel endothelium by purinoceptor stimulation (Martin & Michaelis, 1989;Pirotton et al, 1990). Endothelial cells from different regions of the vasculature exhibit a high degree of variability in ultrastructural (Majno, 1965) and biochemical (Gerritsen, 1987) characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Internalization and degradation of TM may be induced and is followed by increased TM expression due to PMA-induced up-regulation of TM mRNA. However, it may be possible that enhancement of TM activity by prolonged incubation with PMA results from down-regulation of protein kinase C, after activation of the enzyme, in cell membranes as reported by Pirotton et al (1990) in bovine aortic endothelial cells.…”
Section: Time Course Of Surface Tm Activity and Total Tmmentioning
confidence: 93%
“…These results could have some significance in wound healing, for it has been pointed out that wound healing is defective in paraplegics and in areas of facial paralysis. Recent studies have provided evidence for increased formation of phosphatidic acid (PA) by ATP in endothelial cells via stimulation of phosphatidylcholine (PC) breakdown (Martin and Michaelis, 1989;Pirotton et al, 1990). The mitogenic effect of PA (reviewed in Knauss et al, 1990) and of lysophosphatidic acid (LPA) (van Corven et al, 1989) were recently reported.…”
Section: Interactions Between Extracellular Atp and Autocrine/paracrimentioning
confidence: 99%